Rapid Results!: How 100-Day Projects Build the Capacity for Large-Scale Change - and Schaffer, Robert H.; Ashkenas, Ron (Jossey-Bass, 2005)
Rapid Results! shows how to make large-scale changes succeed by using 100-day results-producing projects to develop this vital implementation capability. Written by Robert H. Schaffer, Ronald N. Ashkenas, and their associates—leaders in the field of change management—Rapid Results! describes an approach that has been field-tested by real organizations of every size and description to improve performance and speed the pace of change. Rapid results projects produce results quickly, introduce new work patterns, and enable participants to learn a variety of lessons about managing change. Step by step, the book describes how the use of rapid-cycle, or 100-day, projects will multiply your organization’s power to succeed at large-scale change. Schaffer and Ashkenas specifically outline the concept behind 100-day projects and show you how to Set up the architecture to implement rapid results projects Improve operational performance and also attain hard results in the soft areas of management Build rapid results into major organizational change such as reorganization, acquisition integration, and international development Use rapid results to drive leadership development and culture change